From Research to Practice in the Design of Cooperative Systems: Results and Open Challenges 2012
DOI: 10.1007/978-1-4471-4093-1_4
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Virtual Space of Academia

Abstract: The aim of this chapter is to provide a view on how researchers present themselves in a social network specifically developed for supporting academic practices, how they share information and engage in dialogues with colleagues worldwide. We analysed data from 30,428 who have registered on a publicly available website to study the effect of academic position, university ranking and country on people's behaviour. Results suggest that the virtual network closely mirrors physical reality, reproducing the same hie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 16 publications
(31 reference statements)
4
30
1
Order By: Relevance
“…Very few EHC researchers had profiles in Mendeley and Academia.edu. A previous study (Menendez et al 2012) found that more users of Academia.edu (for their dataset) worked in research institutions in North America (38%), than in Europe (21%; more than half in the UK). This suggests that Academia.edu is not so popular for European scholars, maybe with exception of these working in United Kingdom.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Very few EHC researchers had profiles in Mendeley and Academia.edu. A previous study (Menendez et al 2012) found that more users of Academia.edu (for their dataset) worked in research institutions in North America (38%), than in Europe (21%; more than half in the UK). This suggests that Academia.edu is not so popular for European scholars, maybe with exception of these working in United Kingdom.…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, few studies have investigated this tool (e.g., Menendez et al 2012;Thelwall and Kousha in press).…”
Section: Identification Of Scientists' Web Presencesmentioning
confidence: 99%
“…Likewise, SNS have been found to be used by academics as tools for forming digital identities and engaging in impression management (Veletsianos, 2012). Many academics use social media in order to increase the visibility of their research and discuss their ideas with their colleagues (Lupton, 2014;Menendez et al, 2012). We suggest that academics' need for selfpromotion, which is the manifestation of someone's abilities or accomplishments in order to be seen as competent by others (Bolino and Turnley, 1999) and enhancement of professional identity, affects their attitude towards using online technologies for engagement in a positive way.…”
Section: Self-promotion and Imagementioning
confidence: 99%
“…SNS are used for information dissemination in academia too (Lupton, 2014;Menendez et al, 2012). More specifically, many academics use SNS in order to keep in touch with new developments and events and provide access to new or unpublished articles in their research field (Lupton, 2014).…”
Section: H2: Academics' Need To Maintain a Positive Image Positively mentioning
confidence: 99%
See 1 more Smart Citation